The Criminal Justice System’s Interventions toward Crime Victimization: Aims and Challenges - Bhanu Prakash Nunna; Gerd Ferdinand Kirchhoff; Manjushree Palit (Fakultas Hukum Universitas Surabaya, 2022)
The crime victim frequently suffers psychological/emotional damages along with physical, financial, and social damages. Understanding the damages victims suffer is essential in complex victim care. Individuals, criminal justice institutions, and victim support organizations attending to a victim post-victimization must be mindful of these damages to assist better and avoid further emotional damage in the form of secondary victimization. We accept the Criminal Justice System (CJS) as a given solution to criminalizable situations in society. There are enough indicators that challenge its effectiveness and use. In fact, our belief in its function is not based on any facts. In this paper, we examine where we fundamentally went wrong in our concepts of the criminal justice system; from crime to punishment and rehabilitation of offenders, from victimization to justice, and victim support. Furthermore, the article identifies some of the challenges that professionals in CJS and victim support face, including a fundamental belief that “victims are revengeful”, professional language use, and scientific knowledge limitations.